APOE protects against severe infection with Mycobacterium tuberculosis by restraining production of neutrophil extracellular traps. - Dong Liu; Dat Mai; Ana N Jahn; Tara A Murray; John D Aitchison; Benjamin H Gern; Kevin B Urdahl; Alan Aderem; Alan H Diercks; Elizabeth S Gold (PLoS Pathogens)
Mice lacking apolipoprotein E (APOE, Apoe-/- mice) on a high cholesterol (HC) diet are highly susceptible to infection with Mycobacterium tuberculosis (Mtb) but the underlying immune dysregulation has been unclear. While neutrophils are often the predominant cell type in the lungs of humans with severe tuberculosis (TB), they are relatively scarce in the lungs of some strains of mice that are used to study the disease. The neutrophil levels in the lungs of Mtb-infected Apoe-/- HC mice are very high, and thus studies in this model offer the opportunity to examine the role of specific neutrophil functions in the pathology of severe TB. We determined that depleting neutrophils, depleting plasmacytoid dendritic cells (pDCs), or blocking type I interferon signaling improved the outcome of TB in Apoe-/- HC mice. We also demonstrated that blocking the activation of peptidylarginine deiminase 4 (PAD4), an enzyme critical to NET formation, leads to fewer NETs in the lungs and dramatically improves the outcome of TB in Apoe-/- HC mice without affecting the number of neutrophils in the lung. We found that the transcriptional profile of neutrophils in Mtb-infected Apoe-/- HC mice is biased towards a state that resembles the "N2" phenotype that has been defined in cancer models and has been implicated in matrix degradation and tissue destruction. Our observations strongly suggest that the state of the neutrophil when it encounters the Mtb-infected lung is one of the main drivers of severe disease and implies that targeted interventions that alter specific states or functions, such as the production of NETs, may improve outcome while preserving sufficient capacity for host-defense.